O processo de inovação social como resposta aos vazios institucionais : uma análise multidimensional em diferentes contextos sociais - Agostini, Manuela Rösing (Universidade do Vale do Rio dos Sinos, 2017)
In an international scenario characterized by social inequalities, rising poverty rates and market dissymmetry, an increasing number of researchers have investigated different theories that seek to reconcile management practices and search for innovative solutions to social transformation. According to this perspective, this thesis aims to understand the process of social innovation and the factors that influence social innovation initiatives in contexts of institutional voids. Thus, social innovation is understood as the development of new solutions that generate an impact in solving social problems, involving actors and stakeholders in promoting a change in social relations, transforming local realities. Institutional voids occur when institutional arrangements do not allow the full functioning of the market leading to innumerable social inequalities, either through the absence, weakness or non-fulfillment of the role that is expected from the institutions that form the social context. In order to investigate social innovation initiatives in contexts of institutional voids, this thesis followed six methodological steps, the first one inspired in an exploratory case in an indigenous community that produces organic coffee in southern Mexico. The second step is a literature review with the identification of preliminary research proposals that were investigated in two other case studies in Brazil, one in the south and the other in the north of the country. With these cases, it was possible to reformulate the preliminary propositions, generating a document with seven proposals validated by researchers that integrate research groups in social innovation. This thesis followed the interpretative paradigm, with a qualitative research approach. Among the main results, there is the strong relationship between social innovation and the institutional context in which it is inserted, leading to the first theoretical contribution of this thesis: the presence of institutional voids intensifies social inequalities in contexts of socioeconomic vulnerability and social innovations can act to fill or soften these voids. This thesis still advances in theory by including the perspective that institutional voids originate not only from the State, market and non-profit organizations, as addressed in literature, but also from science and community rules and cultures. It was also identified that voids can also occur in contexts with a developed market and with a high concentration of institutions. Moreover, institutional voids are filled by multiple actors who have different and complementary goals and can act together in social transformation. However, for this transformation to be effective, the values, norms and culture of the actors involved must be respected through a shared negotiation of collective ideals. Another highlight is the identification of five systems to analyze the context in which social innovation initiatives are inserted: political, financial, economic, education/work, and cultural. The last theoretical contribution that this thesis presents refers to the possibility of a hybrid formation of institutions to fill institutional voids, being composed by the local communities and by dominant institutions in the institutional scenario.
Keywords: Inovação social; Vazios institucionais; Análise multidimensional; Contexto social; Sistemas institucionais; Social innovation; Institutional voids; Multidimensional analysis; Social context; Institutional systems; ACCNPQ::Ciências Sociais Aplicadas::Administração